A cross sectional study of the parent’s willingness to vaccinate children of age group between 5-12 years against covid-19 - Vishvamohini D. Bugade; Vikas D. Kshirsagar; Malangori A. Parande; P.S. Borle; Muralidhar P. Tambe; Ganesh Jagadale; Namrata Mule (Al Ameen Journal of Medical Sciences, 2023)
Introduction: The emerging respiratory illness caused by SARS-CoV-2 has posed the threat to human life across the globe. Various physical measures applied to curb the spread of the virus in initial phase of pandemic but high level of immunity by vaccination is an effective strategy to reduce the morbidity and mortality. To achieve this parent’s willingness is important for vaccination of children. Objectives: To study the parent’s willingness and associated factors to vaccinate the children with Covid-19 vaccine. Material & Methods: The cross sectional study conducted in the month of July 2022. A confidential interview of 300 parents visited to OPD was taken. Information obtained about socio-demography, routine immunization and comorbidity in children, parents COVID-19 vaccination, COVID-19 infection and hospitalization in family members and willingness for children’s covid-19 vaccination. Results: Out of 300 parents around 253(84.3%) parentswere willing, 10(3.3%) not willing and 37(12.3%) not sure about children’s vaccination. hospitalization of family members, parental vaccination against Covid-19, vaccination of siblings > 12 years, parents having 1-2 children were significantly associated with willingness. Conclusion: Counselling of parents to relieve the anxiety is needed, communicating clear information about vaccination and expected side effects of the vaccine, provision of reliable source of information like family physician, health care workers.